Analysis of Risk Management Strategies of PT. Asuransi Takaful Keluarga during the Covid-19 Period in Area of Sumatra 1 - Putri, Rafika Chudriana; Rahim, Abdul; Nurlaila, Nurlaila (Budapest International Research and Critics University, 2022)
The purpose of this study is to determined the risk management strategy of PT Asuransi Takaful Keluarga using the SWOT and QSPM methods. The results of the risk strategy include: Placement of greater funds on investment, digital product branding, having marketers who would raise the Sharia economy, having SOPs and filing claims independently, continuing to pay Covid-claims, having sufficient capital, and maintaining credibilities. The results of the SWOT method show that the company is in quadrant I, which are carrying out an aggressive strategy by using the company's strengths to take advantage of every opportunity. The results of the QSPM method show five Priority Strategy: to take advantage of digital Sharia insurance brands to attract Muslim customers to avoid usury, increase marketers from preachers community, improve online service and information facilities, increase understanding and collaborate with local Islamic institutions which have no branches and enhance promotion and branding of company through digital tools.